THE MODEL FOR THE DEVELOPMENT OF PROFESSIONAL LEARNING COMMUNITY TO ENHANCE LEARNING ACHIEVEMENT OF BASIC SCHOOLS IN KAMPHAENG PHET PROVINCE - Kongtongnok, Wisakul; Robchanachai Poolsuk, Pitsamai; Phornwiang, Suban (Journal of Buddhist Anthropology, 2020)
The purposes of this research were to 1) study the schools’ conditions and the problems as professional learning communities to enhance learning achievement, 2) establish a model to improve the schools’ professional learning community, 3) investigate and evaluate the model, and 4) develop a manual and evaluate the implementation of the model. The subjects of this qualitative study included 35 school administrators and 319 teachers. The data were collected by using documentary research, a questionnaire, and a structured interview with successful schools. The data were analyzed by using percentage, frequency, means and standard deviation. The results revealed that, in terms of the conditions of academic work, budgeting, personnel, and general administration were operated based on the scope of Ministry of Education. As for the conditions of the development of professional learning community to enhance learning achievement, it was found that the preparation, operation, supervision, monitoring, evaluation, improvement, and knowledge dissemination were operated but they were done continuously. The results also showed that the problems of the academic work, personnel , and general administration were at a high level; whereas, budgeting was at the highest level. In terms of the development, the problems of preparation, operation, supervision, monitoring, evaluation, improvement, and knowledge dissemination were at the highest levels. As for the model development of the schools in Kamphaengphet, it was found that the model consisted of 7 components: principles, objectives, structure, process, conditions of success, evaluation, and school’s accomplishment. The investigation and the evaluation of the model indicated that the appropriateness, the possibility, and the utility were at the highest levels. In addition, the appropriateness of the manual and the evaluation form were at the highest level.